Incomplete insertion of pedicle screws triggers a higher biomechanical risk of screw loosening: mechanical tests and corresponding numerical simulations - Yang, Jie-Xiang; Luo, Lin; Liu, Jin-Hui; Wang, Nan; Xi, Zhi-Peng; Li, Jing-Chi (Frontiers in Bioengineering and Biotechnology, 2024)
Screw loosening is a widely reported issue after spinal screw fixation and triggers several complications. Biomechanical deterioration initially triggers screw loosening. Studies have shown that incomplete insertion of pedicle screws triggers a higher risk of screw breakage by deteriorating the local mechanical environment. However, whether this change affects the risk of screw loosening biomechanically has not been identified. This study conducted comprehensive biomechanical research by polyurethane foam mechanical tests and corresponding numerical simulations to verify this topic. Pedicle screw-fixed polyurethane foam models with four different insertional screw depths were constructed, and the screw anchorage ability of different models was verified by toggle tests with changed and constant loads. Moreover, the stress distribution of screw and bone-screw interfaces in different models was computed in corresponding numerical mechanical models. Mechanical tests present better screw anchorage ability with deeper screw insertion, but parameters present no significant difference between groups with complete insertion of threads. Correspondingly, higher stress values can be recorded in the model without complete thread insertion; the difference in stress values between models with complete thread insertion was relatively slight. Therefore, incomplete thread insertion triggers local stress concentration and the corresponding risk of screw loosening; completely inserting threads could effectively alleviate the local stress concentration and result in screw loosening.